EFEK PROTEKTIF BUNGA CEMPAKA KUNING (MICHELIA CHAMPACA L.) TERHADAP SEL ENDOTEL PEMBULUH DARAH PADA TIKUS USIA MENOPAUSE - Nora Veri; Alchalidi Alchalidi; T. Iskandar Faisal; Nuswatul Khaira (JKM (Jurnal Kebidanan Malahayati), 2021)
PROTECTIVE EFFECT OF CEMPAKA KUNING FLOWER (MICHELIA CHAMPACA L.)  ON ENDOTEL CELLS OF VASCULAR IN MENOPAUSAL AGE RATS Background: The trend of coronary heart disease (CHD) in menopausal women has now changed to be faster (between 8-10 years). Endothelial dysfunction is usually an indicator of future cardiovascular problems. The main risk factor will cause the integrity of endothelial cells to be impaired and change the function of indothelial cells to release cytokines to initiate inflammation. Treatment of Michelia Champaca L. flowers containing essential oils, alkaloids, sterols and terpenoids, saponins, polyphenols, flavonoids, and glycosides is expected to reduce the risk of CHD in menopausal women due to hypoestrogens.Purpose: To determine the protective effect of ECK on vascular endothelial cells.Methods: The research design used was true experimental design with the randomized posttest only control group design approach. This study used experimental mice which were grouped into 3 groups, namely the control group and two intervention groups. Observation of the number of endothelial cells was carried out after the treatment of cempaka kuning flower extract at a dose of 100 mg / Kg.BW / day and 200 mg / Kg.BW / dayResults: here was a significant difference in the mean number of endothelial cells in menopausal rats due to ECK administration compared to the control groupConclusion: ECK was able to increase the number of endothelial cells in menopausal rats. Further research is needed on the effects of ECK as phytoestrogensSuggestion Further research is needed on the effects of ECK as phytoestrogens. Keywords: Michelia Champaca, Coronary Heart Disease, Endothelial Dysfunction, Menopausal ABSTRAK Latar Belakang : Kejadian Penyakit Jantung Koroner (PJK) pada wanita menopause menunjukkan perubahan kejadian, dimana sekarang usia wanita terkena PJK menjadi lebih cepat (antara 8-10 tahun). Disfungsi endotel biasanya merupakan indikator kejadian PJK pada masa yang akan datang. Faktor resiko tersebut akan menyebabkan perubahan fungsi sel endotel dalam memproduksi sitokin pro inflamasi. Terapi Ekstrak Bunga Cempaka Kuning (ECK) yang mengandung essential oils, alkaloid, sterol, terpenoid, saponin, polyphenol, flavonoid  dan glycoside mampu menurunkan kejadian PJK pada wanita menopause akibat hipoestrogen.Tujuan : Untuk mengetahui efek protektif ECK pada sel endotel pembuluh darah.Metode : Rancangan penelitian yang digunakan adalah true experimental design dengan pendekatan the randomized posttest only control group design. Penelitian ini menggunakan hewan coba tikus yang dikelompokkan kedalam 3 kelompok yaitu kelompok kontrol dan dua kelompok intervensi. Pengamatan jumlah sel endotel dilakukan setelah perlakuan pemberian ekstrak bunga cempaka kuning dosis 100 mg/Kg.BB/hari dan 200 mg/Kg.BB/hariHasil  : Terdapat perbedaan yang bermakna rerata jumlah sel endotel pada tikus usia menopause akibat pemberian ECK dibandingkan kelompok controlKesimpulan : ECK mampu meningkatkan jumlah sel endotel pada tikus usia menopause. Diperlukan penelitian lanjutan tentang efek ECK sebagai fitoestrogenSaran Diperlukan penelitian lebih lanjut tentang efek ECK sebagai fitoestrogen. Kata Kunci : Michelia Champaca L., Penyakit jantung Koroner, Disfungsi Endotel, Menopause